General chemistry - Steven D Gammon (Canada Nelson Education Ltd, 2013)
Covers principles of chemistry, descriptive inorganic chemistry, organic chemistry, and biochemistry. Includes two molecular visualization programs, interactive exercises, three-dimensional molecular models, and more than 150 full-motion videos showing chemical reactions in progress.
includes index
System requirements for Windows: Pentium; 64MB RAM; Windows 98/NT 4/Me/2000; 16-bit color with 800 x 600 resolution; 8X CD-ROM drive.
System requirements for Macintosh: Power Macintosh; 64MB RAM; System 8.5.1 or higher; 800 x 600 resolution; 8X CD-ROM drive.
Keywords: Chemistry